Zooming in on accretion: I. The structure of halo gas - Nelson, Dylan; Springel, Volker (Monthly notices of the Royal Astronomical Society, 2016)
We study the properties of gas in and around 1012 M⊙ haloes at z = 2 using a suite of high-resolution cosmological hydrodynamic ‘zoom’ simulations. We quantify the thermal and dynamical structure of these gaseous reservoirs in terms of their mean radial distributions and angular variability along different sightlines. With each halo simulated at three levels of increasing resolution, the highest reaching a baryon mass resolution of ∼10 000 solar masses, we study the interface between filamentary inflow and the quasi-static hot halo atmosphere. We highlight the discrepancy between the spatial resolution available in the halo gas as opposed to within the galaxy itself, and find that stream morphologies become increasingly complex at higher resolution, with large coherent flows revealing density and temperature structure at progressively smaller scales. Moreover, multiple gas components co-exist at the same radius within the halo, making radially averaged analyses misleading. This is particularly true where the hot, quasi-static, high entropy halo atmosphere interacts with cold, rapidly inflowing, low entropy accretion. Haloes at this mass have a well-defined virial shock, associated with a sharp jump in temperature and entropy at ≳ 1.25 rvir. The presence, radius, and radial width of this boundary feature, however, vary not only from halo to halo, but also as a function of angular direction, covering roughly ∼75 per cent of the 4π sphere. We investigate the process of gas virialization as imprinted in the halo structure, and discuss different modes for the accretion of gas from the intergalactic medium.
Gesehen am 06.11.2017